2018
DOI: 10.24996/ijs.2018.59.1b.5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity among wheat selectedegenotypese and local varieties for saltetolerance by usingeRAPD and ISSR analysis

Abstract: Three genotypes of wheat developede for saltetoleranceethroughe plant breeding program and two local cultivars were screened for genetic variation under salinity conditions through RAPD and ISSR markers. Eight selected primers (OP1-06, OPE-16, OPN-07, OPO-17, OPD-20, OPL-05, OPI-01 and OPJ-13) were used in randomeamplifiede polymorphic eDNA (RAPD-PCR reaction) and three selected primers (UBC 809, UBC 810 and UBC 811) were used in ISSR markers. According to the results of the amplification and ISSR markers, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Through these results, it was found that there is a degree of genetic similarity or diversity between the genotypes included in the study, and this is due to two things, first the difference between the five genotypes may be in the phenotypes, and this is the result of the influence of the environment, which is what depends on it in many breeding programs, second it may be the result of a genetically high similarity between the genotypes, which contradicts the first thing, which depends on phenotypes, and this is due to the similarity in the noncoding regions of genes [27]. This is consistent with many researchers who used the indicators of molecular markers, especially the ISSR, including the study [12,24,26,28,29].…”
Section: Acknowledgementsupporting
confidence: 67%
See 1 more Smart Citation
“…Through these results, it was found that there is a degree of genetic similarity or diversity between the genotypes included in the study, and this is due to two things, first the difference between the five genotypes may be in the phenotypes, and this is the result of the influence of the environment, which is what depends on it in many breeding programs, second it may be the result of a genetically high similarity between the genotypes, which contradicts the first thing, which depends on phenotypes, and this is due to the similarity in the noncoding regions of genes [27]. This is consistent with many researchers who used the indicators of molecular markers, especially the ISSR, including the study [12,24,26,28,29].…”
Section: Acknowledgementsupporting
confidence: 67%
“…The cluster diagram shown in Figure 1 represents the five genotypes of the bread wheat crop used in the study. It was divided into two main groups, the first group included the which determines the genetic fingerprint of the variety [26], variation in bundles is the result of induced mutations or selfmutations that affect the distance between genetic loci that occur naturally during the evolutionary process that occurs in living organisms, the variation may have occurred by addition or deletion at the sites to which the primer is attached, This is what found in other studies [27,28], and the molecular sizes of the multiplicative bundles of the primers included in the study ranged between (2200-350 bp). This agrees with [28] (Table 8).…”
Section: Cluster and Of Principal Components Analysis Based On Molecu...mentioning
confidence: 99%